Parrhesia as journalism: Learning from the truth- and justice-seeking women journalists of twentieth century Turkey - Burce Celik; Nazan Haydari (2022)
Despite ongoing endeavours to decolonize and de-westernize journalism studies, the current literature offers very few clues about the history of women’s journalistic practices and struggles in Third World/Global South contexts. The objective of this article is to help to fill this gap by focusing on the lived experiences and struggles of key Turkish-speaking women journalists who worked in private and public sector media outlets in Turkey in the period 1920 to 1980. Drawing on these women’s self-narratives and biographical accounts, as well as arguments in debates on parrhesia and emancipatory journalism in dialogue with Third World/Global South feminist epistemologies, we explore the ways in which journalism has been a site of life-time resistance and struggle for women seeking justice and truth on behalf of the oppressed. Their conceptualization of journalistic identity as truth- and justice-seekers in an unfree media environment, and their determination to speak the truth to challenge intersecting forces of domination cannot be captured in the binary of “media freedom” and “media development” paradigms. Nonetheless, their struggle to dismantle oppressive reality by way of distinctive, courageous, justice-seeking and truthful communication can be educative at a time when the relationship between journalism and truth is increasingly being undermined.